Fluorescein-Labeled Goat Milk Antibodies: Use in Detection of Mumps Virus in Tissue Culture - Sattar, Syed A. (1967)
Specific antibodies are found in the globulin fraction of the milk following instillation of mumps virus in the mammary gland of the goat. These antibodies, conjugated with fluerescein isothiocyanate, have been successfully employed in the direct fluorescent antibody staining of mumps virus in infected BS-C-1 cells.